A systematic review of community psychosocial group interventions for adults with intellectual disabilities and mental health conditions. Issue 1 (1st August 2021) - Bourne, Jane; Harrison, Toni Leigh; Wigham, Sarah; Morison, Cindy‐Jo; Hackett, Simon
Abstract: Background: People with intellectual disabilities have a high risk of developing mental ill‐health. Treatment is often neglected and diagnosis is misattributed to a person's disability. Standard psychosocial interventions can improve a person's well‐being. This review aimed to understand what interventions are being delivered, any benefits, and future recommendations. Methods: Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines were followed, and the review registered with PROSPERO—CRD42020160254. Databases searched included: MEDLINE, Embase, and PsycINFO. A framework synthesis approach was used to present the findings. Results: There are limited psychosocial interventions offered for this population. When groups are delivered having a creative element, multiple activities over a short period of time, with breaks and group rules outcomes can be improved. Conclusions: Adaptations and reasonable adjustments should be used specifically to a person's ability. A mixed‐method design allows people to share their experiences alongside quantitative data that provides clinical information.